The Changing Character of the California Sierra Nevada as a Natural Reservoir. Issue 23 (3rd December 2018) - Rhoades, Alan M.; Jones, Andrew D.; Ullrich, Paul A.
Abstract: The mountains of the Western United States provide a vital natural service through the storage and release of mountain snowpack, lessening impacts of seasonal aridity and satiating summer water demand. However, climate change continues to undermine these important processes. To understand how snowpack may change in the headwaters of California's major reservoirs, the North American Coordinated Regional Climate Downscaling Experiment is analyzed to assess peak water volume, peak timing, accumulation rate, melt rate, and snow season length across both latitudinal and elevational gradients. Under a high‐emissions scenario, end‐of‐century peak snowpack timing occurs 4 weeks earlier and peak water volume is 79.3% lower. The largest reductions are above Shasta, Oroville, and Folsom and between 0‐ and 2, 000‐m elevations. Regional climate model and global forcing data set choice is important in determining historical snowpack character, yet by end century all models show a significant and similar decline in mountain snowpack. Plain Language Summary: Mountains are natural water towers that store snowpack in winter and release it as snowmelt during spring to summer. However, climate change has and continues to undermine this natural service. To answer where and when water resource management may be impacted by a future of low‐to‐no snowpack, we can leverage climate models, which are able to project the future conditions of mountain snowpack under various assumptions of global greenhouse gas emissions. In this study, we use five unique climate models under a high‐emissions scenario to evaluate a set of snowpack measures upstream of 10 California reservoirs. These 10 reservoirs represent nearly half of California's surface storage and by end century could face a 79% reduction in peak snowpack water volume. This work provides detailed guidance on the mountain snow conditions policymakers, water managers, and scientists will encounter in addressing adaptive resiliency in the face of climate change. Key Points: The historical role of California's Sierra Nevada mountain snowpack as a steady source of fresh water is fading due to climate change Across nine climate simulations historical snow representation varied but by end century agree on the magnitude and direction of decline Under a high‐emissions scenario, a 79.3% decline in peak snow upstream of 40% of California's reservoir storage is shown by end century